Dinamika integrasi kurikulum pesantren modern dan salaf - Hilmi, Annafik Fuad; Ramadhan, Muhammad Rizqi; Daroini, Slamet (Maliki Interdisciplinary Journal, 2025)
This article discusses the integration of traditional (salaf) and modern curricula at MSAA Mabna Al-Ghazali as a response to contemporary Islamic education challenges. This research aims to create harmony between the classical Islamic scholarly tradition through the teaching of the yellow book (kitab kuning) and technology-based modernization, in order to produce graduates who are religious and globally competent. A qualitative method is used to analyze the process of curriculum integration, which includes the implementation of traditional methods such as bandongan and sorogan. The results of the study show that the integration of the curriculum is carried out systematically, starting from the identification of the main elements of both approaches, the gradual implementation of the curriculum, to continuous evaluation. Despite facing challenges such as resistance from educators to innovation and limited resources, the support of pesantren management and the quality of educators significantly contribute to the success of this program. The positive impacts of this curriculum integration include strengthening spirituality, improving critical thinking skills, and preparing graduates to compete at a global level. Therefore, this approach not only becomes an ideal model for the development of other pesantren but also proves that Islamic tradition can be synergized with modernity without sacrific core values.